2009
DOI: 10.1021/jm900513a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation, and Structure−Activity Relationships for 5-[(E)-2-Arylethenyl]-3-isoxazolecarboxylic Acid Alkyl Ester Derivatives as Valuable Antitubercular Chemotypes

Abstract: Tuberculosis (TB), mostly caused by Mycobacterium tuberculosis (Mtb), is one of the leading causes of death from infectious disease worldwide. Its coinfection with HIV and the emergence of multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB) strains have further worsened the TB pandemic. Despite its global impact, TB is considered a neglected disease and no new anti-TB therapeutics have been introduced over the last four decades. The nonreplicating persistent form of TB (NRP-TB) is respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…35 However, Pieroni and co-workers synthesized pyrido-benzimidazoles with submicromolar activity against drug resistant replicating mycobacteria. 36 …”
Section: Resultsmentioning
confidence: 99%
“…35 However, Pieroni and co-workers synthesized pyrido-benzimidazoles with submicromolar activity against drug resistant replicating mycobacteria. 36 …”
Section: Resultsmentioning
confidence: 99%
“…The excellent anti-TB activity and the satisfactory metabolic profile of 5a, led to the development of a simplified series of compounds bearing a trans-ethenyl linker, in which the quinoline moiety was replaced with a benzene or pyridine ring [19]. Various substituents and substitution patterns in the rings were investigated allowing plausible SAR to be derived for the 5-[(E)-2-arylethenyl]-3-isoxazolecarboxylic acid alkyl ester derivatives (for examples see Table 2, 6a-6d).…”
Section: Second Generation Isoxazole-based Anti-tb Compoundsmentioning
confidence: 99%
“…These compounds were screened against M. tuberculosis H37Rv (ATCC 27294) in triplicate at the single concentration of 6.25 mg/mL for inhibitory activity by BACTEC 460 radiometric methods [38,39]. It was found that naphthalene series compounds (22)(23)(24)(25)(26)(27)(28)(29)(30) possess superior anti-TB activity than the quinoline series compounds (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). (Table 2).…”
Section: Antimycobacterial Activitymentioning
confidence: 99%
“…Quinoline-based well-known drug mefloquine is widely used for the prophylaxis of chloroquineresistant Plasmodium falciparum malaria [16,17]. Mefloquine is also known for its antibacterial [18] and anti-tubercular activity [19][20][21][22] (H37Rv MIC range: 8-16 mg/mL or 21.1-42.2 mM) [23] and its analogs have displayed moderate [24] to submicromolar [25] anti-TB activity. Mefloquine and its derivatives are known to act as purine receptor antagonists [26] and it's only prokaryotic target known so far is F 0 F 1 H þ ATPase in Streptococcus pneumoniae [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation